GLP-1 Induces the Expression of FNDC5 Derivatives That Execute Lipolytic Actions - Li, Hui; Donelan, William; Wang, Fang; Zhang, Peilan; Yang, Lijun; Ding, Yousong; Tang, Dongqi; Li, Shiwu (Frontiers in Cell and Developmental Biology, 2021)
Multiple GLP-1-derived therapeutics are clinically used to treat type 2 diabetes and obesity. However, the underlying mechanism of how these drugs regulate the body weight of obese patients remains incompletely understood. Here, we report that the lipolysis effects of GLP-1 on β cells can depend on its induced expression of fibronectin type III domain containing 5 (FNDC5). The transmembrane FNDC5 is a precursor of the recently identified hormone irisin that possesses a range of bioactivities, including anti-obesity and anti-diabetes. We revealed that GLP-1 upregulates the expression and secretion of FNDC5 in β cells, while GLP-1 itself fails to activate the lipolysis genes in FNDC5-knockout β cells. In addition, liraglutide, a clinically used GLP-1 receptor agonist, induced the expression of FNDC5 in mouse pancreas and brain tissues and increased the serum level of secreted FNDC5. Furthermore, we observed the expression of the well-known membrane-associated FNDC5 and a novel, secretable FNDC5 (sFNDC5) isoform in β cells and multiple rat tissues. Recombinant sFNDC5 stimulated lipolysis of wild type and FNDC5-knockout β cells. This new isoform further induced lipolysis and browning of adipocytes, and similar to irisin, executed potent anti-obesity activities in an obese mouse model. Overall, our studies provided new mechanistic insights into GLP-1’s anti-obesity actions in which GLP-1 induces the secretion of FNDC5 derivatives from its responsive organs that then mediate its anti-obesity activities.